Effect of cellulose nano fibers and nano clays on the mechanical, morphological, thermal and dynamic mechanical performance of kenaf/epoxy composites. (1st July 2020) - Khan, Anish; Asiri, Abdullah M.; Jawaid, M.; Saba, N.; Inamuddin
Highlights: Effect of CNF, and nanoclays (MMT and OMMT)) on the performance of kenaf/epoxy composites were investigated. Incorporation of OMMT and CNFs enhanced the mechanical and thermal performance compared to MMT/kenaf/epoxy composites. The obtained results revealed that OMMT and CNFs hybrid nanocomposites can be an efficient alternative for structural applications. Abstract: The aim of the present research work has focused on investigating the effect of cellulose nanofibers (CNFs) and nano clays (montmorillonite (MMT) & organoclay (OMMT)) at 0.75Wt % on the performance of kenaf/epoxy composites. Mechanical (tensile and flexural) and thermal properties of composites in terms of morphology, thermal stability, weight loss, and dynamic mechanical properties were analyzed. The obtained results revealed that the integration of stiff CNFs as filler enhanced the mechanical and thermal properties, storage and loss modulus while a considerable decrease in Tan δ was realized compared to kenaf/epoxy composites. Enhancement in the properties was observed for OMMT and CNFs composites compared to MMT/kenaf/epoxy composites, which is attributed to the uniform filler distribution and interfacial adhesion between CNFs, OMMT, kenaf and epoxy matrix. The obtained results revealed that OMMT and CNFs based kenaf/epoxy composites can be an efficient alternative for construction applications.